Cora Coralina: uma leitura ecofeminista - Macedo, Fabiana Lula (2023)
In this doctoral thesis, I aimed to demonstrate that Cora Coralina's work could be read by the bias of the ecofeminist approach. First, I introduced the author who wrote poems, short stories and chronicles. Her biography impresses with the confrontation of the setbacks that a woman of her time went to be recognized as a writer, so much so that she only came to publish books in old age. Secondly, we present her work as a literature that proves to be a great debtor of modern and modernists. Cora claimed to be self -taught and she was, much of her reader and writer formation happened out of school benches, but she did not write her literary work before having read great authors and in her work we see traces of modernity and modernism. Then we observed the development and importance of ecofeminist studies for ecocrytic. Finally, we present our reading of poems in which the connection between women and nature is present. In some moments in a form with the system that separates culture of nature and, with this, justifies the oppression of women and therefore nature, from the women/ nature and man/ culture connection. At other times we find in poems a Cora who often subvert this system and rejects this hierarchy, establishing a harmonious interaction between men, women and nature. With this, we find in their most telluric poems a kind of continuity between humans and nonhumans living in a much more egalitarian connection. In addition, we also highlighted the poems dedicated to corn. Among so many possible themes, the poet from Goiás writes about a vegetable that until then was not of great prominence within Brazilian literature, but became important to her literature. Nowadays “Oração do Milho” and “Poema do Milho” are two of Cora Coralina's most famous poems.